Code-Switching And Code-Mixing Used By English Teachers At Homy School Palangka Raya - Ipan Dwi Nata, (Jurnal Pendidikan Indonesia, 2021)
Code-switching and code-mixing become one of the issues existing not only in informal situations but also in a formal situations such as in the teaching-learning process. Homy School Palangka Raya, the teacher should speak both Bahasa Indonesia and English which trigger the use of code-switching and code-mixing because this school applied two curriculums: national curriculum K-13 and UK curriculum. So, the objectives of this research are to identify the types of code-switching and code-mixing used by the teachers of English at Homy School Palangka Raya in English class and the influences on students’ understanding of the lessons. This descriptive qualitative research observed and collected the data by joining the class where the teachers were teaching. The research result showed that there were 53 (fifty-three) occurrences of code-mixing, in the form of the insertion of words (11), the insertion of phrase (29), the insertion of hybrid (10), and the insertion of idiom (2). While there were 67 (sixty-seven) occurrences of code-switching in the form of metaphorical (5) and conversational code-switching (30). Regarding the influences of code-switching and code-mixing on the students’ understanding of the English, the lesson revealed that most of the students (seventy-two percents) who claimed that the use of code-switching and code-mixing in the English teaching-learning process at Homy School Palangka Raya can make them understand easily and make their communication with their teacher more effective.